EVALUASI KESESUAIAN LAHAN PERTANIAN PADA AREAL PENGGUNAAN LAIN UNTUK TANAMAN KOPI ARABIKA(Coffea arabica L.) DI KECAMATAN SALAK KABUPATEN PAK-PAK BHARAT - Budi Hartono; Abdul Rauf; Deni Elfiati; Fitra Syawal Harahap; Simon Haholongan Sidabuke (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2018)
Based on the Decree of the Minister of Forestry Number. 44 of 2005 on Appointment of Forest Areas in North Sumatra Province. The total area of forest in Pakpak Bharat Regency based on the decree is 120,711 ha (88.60% of the total of Pakpak Bharat Regency), with details 1) Natural Forest Reserve 4.36%, 2) Limited Production Forest 41.95%, 3) Protection Forest 34.61%, 4) Forest Production 7.68%. Subsequently, the Decree was revised with Decree No. Menhut. 579 / Menhut-II / 2014 in accordance with the proposed revision of forest area by Pakpak Bharat government. With the decree, the forest area released into Other Use Areas (APL) is only a small portion of the proposed area so that APL Land Use (Area of Other Use) in Salak Sub-district needs to be supported with information on land suitability of course very potential land to be utilized in activities cultivation of agriculture, with the hope that productivity can improve the welfare of local people who mostly work as farmers. The objectives of this study were to evaluate the characteristics of the APL land suitability level, to analyze improvement efforts to increase productivity, and to map actual land suitability and potential land suitability for coffee crops on APL land in Salak Subdistrict. The research method used survey method. Unit unit of land based on land map, slope slope map, altitude map, land cover map, and consists of 8 land units and 18 sampling points. Research data were analyzed using matching method. Research results Limiting factors and improvement efforts of plant commodities Coffee Plant (Coffea arabica L.) Rooting factor factor (rc) and nutrient retention (nr). Improvement efforts that can be done is making drainage and calcification CaCo3Key words : Land suitability, Coffee, District Salak